FT-IR and FT-Raman spectroscopic investigations of adsorption of 2,2′-biquinoline by smectite group clay minerals from Anatolia - Davies, J. Eric D.; AKYÜZ, ZEKİ TANIL; AKYÜZ, SEVİM (Elsevier, 2000)
The sorption of 2,2′-biquinoline onto natural and ion-exchanged montmorillonite (Fe-, Co- or Cu-montmorillonite) and saponite from Anatolia have been investigated using FT-IR and FT-Raman Spectrometry. The intercalation of 2,2′-biquinoline within natural and ion-exchanged montmorillonite and saponite has been shown by X-ray diffraction to increase the interlayer spacing. The difference of basal spacing of air-dried clays and biquinoline treated ones shows monolayer arrangement. Raman spectroscopy was particularly useful for investigation of clay-organic interaction. Vibrational spectroscopy indicates that intercalated 2,2′-biquinoline molecules are coordinated to exchangeable cations (directly and indirectly through water bridges) and/or Lewis acid sites or as bidentate ligand.
Keywords: FT-IR; FT-Raman; Clay; Montmorillonite; Saponite; Intercalation; Biquinoline